SWOT ANALYSIS FOR MATERNAL REFERENCE IN HEALTH DEPARTMENT OF SIDOARJO DISTRICT - Kartika Sri Redjeki (Poltekkes Kemenkes Surabaya, 2016)
Background: National Health System briefed the availability of good health services which carriedout with due regard to innovations and breakthroughs in proper implementation, continuous,integrated and plenary through the strengthened of the referral system. The disadvantage ofhealth services is the implementation of referrals less rapid and not precise.Objective: Arranged recommendations related to maternity referral system for HealthDepartment of Sidoarjo DistrictMethods: This was quantitative analytical research. Design of the study was cross-sectional studyusing the method of observation. Samples were employees in the Health Family Section on Healthdepartment of Sidoarjo District. The sample size in this study were 10 people. The samplestechnique was purposive sampling method.Results: First step was observations at Health Family Section of Health Departmen SidoarjoDistrict and analyzed using SWOT, the result was located in quadrant SO (Strength-Opportunity).Based on assessments, the strategy of